2021
DOI: 10.1177/2056305121995788
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Hashtags During Times of Crisis: Analyzing the Broadcasting and Gatekeeping Dynamics of #PorteOuverte During the November 2015 Paris Terror Attacks

Abstract: Twitter hashtags allow citizens to share vital information and make sense of acute crisis events such as terrorist attacks. They also enable those watching from afar to express their sympathy and solidarity with the victims. Perhaps the most well known of these has been #PorteOuverte (translated into English as “Open Door”), first used during the November 2015 terrorist attacks in Paris before re-emerging during subsequent atrocities in Brussels (March 2016) and Nice (July 2016). The hashtag was originally cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Finally, we used repost/retweet network mapping to investigate gatekeeping dynamics (RQ3). This is a technique commonly used to identify prominent users in social media interactions (see Jackson & Foucault Welles, 2015Meraz & Papacharissi, 2013;Reilly & Vicari, 2021;Vicari, 2017). All the network visualizations presented in this paper were produced with Gephi 0.9.2, a network analysis and visualization software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we used repost/retweet network mapping to investigate gatekeeping dynamics (RQ3). This is a technique commonly used to identify prominent users in social media interactions (see Jackson & Foucault Welles, 2015Meraz & Papacharissi, 2013;Reilly & Vicari, 2021;Vicari, 2017). All the network visualizations presented in this paper were produced with Gephi 0.9.2, a network analysis and visualization software.…”
Section: Methodsmentioning
confidence: 99%
“…The focus of these studies is often on discursive dynamics developing on Twitter around the use of issue or activist hashtags (Papacharissi, 2015;Rambukkana, 2015). In more specific terms, research has shown that Twitter's socio-technical infrastructure -especially its affordances enabling bottom-up curation practices -has allowed the coming to prominence of actors who have been traditionally defined as 'non-elite' , namely ordinary users ( Hermida, 2015;Jackson & Foucault Welles, 2015Meraz & Papacharissi, 2013;Reilly & Vicari, 2021;Vicari, 2017;Vicari et al, 2020). These dynamics have then brought changes to traditional gatekeeping practices, with citizens often becoming primary sources of information, or gatekeepers, for both traditional non-elites (i.e.…”
Section: Platforms and Participatory Culturesmentioning
confidence: 99%
“…This illustrates how hashtags capture the attention of tweeters in such a way as that aids the mobilisation of support for social movements and advocacy campaigns (Xiong, et al, 2019). Research indicates that hashtags can be extremely effective in presencing specific narratives, which are often curated by non-elite actors (Meraz and Papacharissi, 2013;Jackson and Foucault Welles, 2016;Vicari, 2017;Reilly and Vicari, 2021).…”
Section: Networked Framing On Twittermentioning
confidence: 96%
“…Researchers have explored the use of hashtags during emergency situations, such as terrorist attacks (Burnap et al, 2014;Steensen, 2018;Tikka, 2019;Reilly & Vicari, 2021) and natural disasters (Bruns & Burgess, 2014;Pourebrahim et al, 2019). For example, Burnap and colleagues (2014) examined Twitter communication during a terrorist attack in Woolwich in 2013.…”
Section: Hashtags and Crisis Eventsmentioning
confidence: 99%